Pentecostals and Roman Catholics on becoming a Christian : spirit-baptism, faith, conversion, experience, and discipleship in Ecumenical perspective - Murphy, Karen R. J. (Global Pentecostal and Charismatic Studies, 2018)
In Pentecostals and Roman Catholics on Becoming a Christian , Dr. Karen Murphy explores the fifth round of the International Roman Catholic-Pentecostal Dialogue (1998-2006). Discussing Spirit-baptism, faith, conversion, experience, and discipleship, Dr. Murphy notes areas in which the Dialogue has evolved since its inception in 1972. She unpacks the commonalities that bond Catholics and Pentecostals and examines theological divergences and challenges to dialogue. While Catholics approach becoming a Christian from a sacramental perspective, most Pentecostals think of Christian initiation in non-sacramental, or conversionist, terms, a reality that fosters ongoing tensions between the two traditions. Dr. Murphy reveals how Catholics and Pentecostals seek to overcome this dichotomy by honoring spirituality and experience as integral to the ecumenical encounter.